PENGARUH KONTRAK UTANG, LITIGACY RISK, DAN STRUKTUR KEPEMILIKAN INSTITUSIONAL TERHADAP KONSERVATISME AKUNTANSI - Kartika Nuranggraeni; Ratih Qadarti Anjilni (ICMA Nasional, 2024)
This research aims to analyze the influence of debt contracts, litigation risk and institutional ownership structure on accounting conservatism. The population used was non-cyclical consumer sector companies for the 2019-2023 research period, the sampling technique used purposive sampling. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The number of samples before classification was 125 and after classification into 14 companies with 5 years of research, 70 samples were used in the research. Furthermore, the research method used is a quantitative research method. The data analysis method uses panel data regression analysis methods, classical assumption tests, significance tests. Meanwhile, data processing uses the help of the Eviews 9 statistical program. The results of the research show that the debt contract variable (X1) has a significant influence on accounting conservatism, then litigation risk (X2) does not have a significant influence on accounting conservatism, whereas institutional ownership structure ( X3) does not have a significant influence on accounting conservatism. This shows that the independent variables debt contracts, litigation risk and institutional ownership structure together (simultaneously) have a significant influence on accounting conservatism.